Room for uncertainty in infrastructure planning : How continuous certainification by decision makers results in more uncertainty - Veenma, Klaas; Leendertse, Wim; Arts, Jos (AESOP, 2023)
An increasingly dynamic environment and engaged society necessitates decision makers in infrastructure planning to adopt adaptive and participative planning approaches and give room to uncertainty in planning and decision making. In planning, individual actors belonging to a group of like-minded actors may attempt to influence decision-making about planning proposals. They do so by using a mix of instruments such as research, participation, agreements, and so on. To gain greater insight into the processes of interactions between decision makers and other relevant actors in planning, the planning of three infrastructure cases – a road upgrade, an airport runway redevelopment, and a river bypass in the Netherlands – was studied in-depth each covering a period of 20 years. Interestingly, a couple of overarching patterns regarding dealing with uncertainty in planning and decision-making appeared from the study. Decision makers continuously strive for ‘certainification’, and do so by deploying authority-based instruments. Indeed, they keep doing so, even if the the result obtained is opposite of that which was desired. Certainification i.e., decision makers striving for reducing uncertainties, often results in a reaction of ‘decertainification’ from opponents. It seems as if decision makers strengthen the latter’s own opposition. And when decision makers actually do give room for uncertainties through adopting an adaptive approach, other actors often demand less uncertainty; driving decision makers back to their thirst for certainification. To overcome this continuous loop, an arena and institutional setting should be created in which actors from different advocacy coalitions are involved in open dialogue to better balance the perceived uncertainties of all stakeholders.
Transactions of the Association of European Schools of Planning; Vol. 7, No. 1 (2023): 36-44
Keywords: infrastructure planning; decision making; advocacy coalition; policy belief; certainification; participation; uncertainty